Efficacy of venetoclax monotherapy in patients with relapsed chronic lymphocytic leukaemia in the post‐BCR inhibitor setting: a UK wide analysis. (15th February 2019) - Eyre, Toby A.; Kirkwood, Amy A.; Gohill, Sat; Follows, George; Walewska, Renata; Walter, Harriet; Cross, Matthew; Forconi, Francesco; Shah, Nimish; Chasty, Richard; Hart, Alistair; Broom, Angus; et al.
Summary: Venetoclax is a BCL2 inhibitor with activity in relapsed/refractory (R/R) chronic lymphocytic leukaemia (CLL). We conducted a multi‐centre retrospective analysis of 105 R/R CLL patients who received venetoclax pre‐National Health Service commissioning. The median age was 67 years and median prior lines was 3 (range: 1–15). 48% had TP53 disruption. At ≥2 lines, 60% received a Bruton Tyrosine Kinase inhibitor (BTKi) and no prior phosphoinositide 3‐kinase inhibitor (Pi3Ki), 25% received a Pi3Ki and no prior BTKi, and 10% received both. Patients discontinued B cell receptor inhibitor (BCRi) because of toxicity in 44% and progression in 54%. Tumour lysis syndrome risk was low, intermediate or high in 27%, 25%, and 48% respectively. Overall response was 88% (30% complete response [CR]). The overall response rate was 85% (CR 23%) in BTKi‐exposed patients, 92% (CR 38%) in Pi3Ki‐exposed patients and 80% (CR 20%) in both ( P = 0·59). With a median follow‐up of 15·6 months, 1‐year progression‐free survival was 65·0% and 1‐year overall survival was 75·1%. Dose reduction or temporary interruption did not result in an inferior progression‐free or discontinuation‐free survival. Risk of progression or death after stopping a prior BCRi for progression was double compared to those stopping for other reasons (predominantly toxicity) (Hazard Ratio 2·01 P = 0·05). Venetoclax is active and well tolerated in R/R CLL post ≥1 BCRi. Reason(s) for stopping BCRi influences venetoclax outcomes.